2017
DOI: 10.1038/ncomms15760
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the elementary structural units of the DNA damage response

Abstract: Histone H2AX phosphorylation is an early signalling event triggered by DNA double-strand breaks (DSBs). To elucidate the elementary units of phospho-H2AX-labelled chromatin, we integrate super-resolution microscopy of phospho-H2AX during DNA repair in human cells with genome-wide sequencing analyses. Here we identify phospho-H2AX chromatin domains in the nanometre range with median length of ∼75 kb. Correlation analysis with over 60 genomic features shows a time-dependent euchromatin-to-heterochromatin repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
182
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(202 citation statements)
references
References 51 publications
19
182
1
Order By: Relevance
“…Our finding that conventionally detected gH2AX foci consist of discrete subunits is further corroborated by the results of recent studies employing superresolution microscopy (13,15). The main achievement of our study is the direct visualization of previously unobserved gH2AXdecorated nucleosomes as elementary structural units of DSB repair foci.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding that conventionally detected gH2AX foci consist of discrete subunits is further corroborated by the results of recent studies employing superresolution microscopy (13,15). The main achievement of our study is the direct visualization of previously unobserved gH2AXdecorated nucleosomes as elementary structural units of DSB repair foci.…”
Section: Discussionsupporting
confidence: 90%
“…Despite numerous studies regarding the involvement of gH2AX in DNA repair, the nanoscale organization of gH2AX and DDR proteins within IR-induced foci remains largely unknown because of the resolution limit of conventional fluorescence microscopy. At present, there are only a few reported studies using superresolution fluorescence microscopy to explore the nanoscale organization of DSB repair foci (13)(14)(15)(16). Those studies revealed that DSB foci consist of several subfoci with a lateral diameter ranging between ;100 and 200 nm.…”
mentioning
confidence: 99%
“…It has been shown that such foci can be separated into functionally relevant sub-foci or clusters of about the same size independent from the dose applied [23,28,29]. This has also been found for the cell nuclei analyzed here (see Figure S2).…”
Section: Resultssupporting
confidence: 78%
“…These clusters are not identical with γH2AX foci obtained by diffraction limited wide-field imaging. It has been shown that the foci are sub-divided into several sub-units which are compatible to the clusters described here [23,28]. Furthermore, the two parameters for the cluster recognition have been varied in order to ensure that the results of the subsequent analysis discussed in the following are not crucially dependent on this choice of parameters.…”
Section: Resultsmentioning
confidence: 93%
“…There are no data in this regard and this question is subject for future consideration. Recent observations [25] shed new light on the mechanisms of DSB and H2AX foci induction and repair within TADs. In the present model TADs participate in exchange aberrations as structural blocks within chromosome of increased frequency of contacts of 100 kbp bins or chromosomal elements.…”
Section: Discussionmentioning
confidence: 99%